2023
DOI: 10.1098/rsos.221443
|View full text |Cite
|
Sign up to set email alerts
|

Here comes the sun: music features of popular songs reflect prevailing weather conditions

Abstract: We examine associations between prevailing weather conditions and music features in all available songs that reached the United Kingdom weekly top charts throughout a 67-year period (1953–2019), comprising 23 859 unique entries. We found that music features reflecting high intensity and positive emotions were positively associated with daily temperatures and negatively associated with rainfall, whereas music features reflecting low intensity and negative emotions were not related to weather conditions. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Health. Finally, it has long been assumed that humans engage with art objects partly in order to regulate emo7ons (Anglada-Tort et al, 2023;Winner, 2018). Central to this idea is the Neurobiology of art no7on that art objects hold the power to change, release, or otherwise modulate people's current emo7onal state (Anglada-Tort et al, 2023).…”
Section: Emo5onal Regula5on In Art Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health. Finally, it has long been assumed that humans engage with art objects partly in order to regulate emo7ons (Anglada-Tort et al, 2023;Winner, 2018). Central to this idea is the Neurobiology of art no7on that art objects hold the power to change, release, or otherwise modulate people's current emo7onal state (Anglada-Tort et al, 2023).…”
Section: Emo5onal Regula5on In Art Contextsmentioning
confidence: 99%
“…Finally, it has long been assumed that humans engage with art objects partly in order to regulate emo7ons (Anglada-Tort et al, 2023;Winner, 2018). Central to this idea is the Neurobiology of art no7on that art objects hold the power to change, release, or otherwise modulate people's current emo7onal state (Anglada-Tort et al, 2023). Analysis of streaming data from Spo7fy has revealed that music listeners differ in the kind of music they prefer to listen to during the day and throughout the week, with so|er music being preferred in the morning and upbeat and energe7c music being preferred in the evenings (Heggli, Stupacher & Vuust, 2021).…”
Section: Emo5onal Regula5on In Art Contextsmentioning
confidence: 99%
“…Second, we tested for potential seasonal effects, as particular months in the year (e.g., holiday seasons, christmas) can link to different consumption patterns 27,102 . We compared the trends in our study with the same months in the following year by computing Pearson correlations between the two trends (Supplementary Fig.…”
Section: Trend Validationmentioning
confidence: 99%